Yields of pyrolysis products from refuse-derived fuel. Issue 4 (16th February 2016) - Li, Yanji; Jiang, Lu; Zou, Kewei; Li, Rundong; Chi, Yong
ABSTRACT: Pyrolysis yields and gas characteristics must be studied to control pollution caused by waste-energy recycling and to develop a refuse-derived fuel technology. In this study, refuse-derived fuel pyrolysis experiments were performed in a high-temperature tube furnace. The effects of the final pyrolysis temperature, material mixture ratio, and pyrolysis rate on the yields of pyrolysis products, including gas, tar, and semi-coke, were studied. The volume fractions of the pyrolysis gas components (H2, CO, CH4, and CO2 ) of the samples were also detected. Results showed that with increased final temperature, the tar and gas yields increased but the semi-coke yield decreased. The volume fractions of the components had the following trends: H2 increased, CO initially decreased and then increased, CH4 initially increased and then decreased, and CO2 decreased. With decreased biomass, the tar yield decreased and then increased, whereas the semi-coke and gas yields increased and then decreased. Compared with slow pyrolysis, fast pyrolysis decreased the tar yield by 9.13%, increased the gas yield by 7.45%, increased the CO and CH4 volume fractions, and decreased the CO2 volume fraction.